2008
DOI: 10.1002/micr.20528
|View full text |Cite
|
Sign up to set email alerts
|

Effect of adrenergic stimulation on cutaneous microcirculation immediately after surgical adventitiectomy in a rat skin flap model

Abstract: Chronic sympathetic denervation leads to the development of supersentivity to adrenergic agents. Free flap surgery results in the disruption of the autonomic nerve fibers running along the anastomosed vessels. We therefore investigated the early effect of surgical sympathectomy on the reactivity of cutaneous microcirculation challenged to adrenergic agents. Two epigastric flaps were elevated and exposed in 15 rats. On the right flap (Side A), a circular adventitiectomy of the feeder vessels was realized to pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 46 publications
0
19
0
Order By: Relevance
“…5,6 The microvascular surgeon's fear of vasopressors likely stems from the belief that these drugs may provoke pedicle vasospasm, which can lead to thrombosis and flap failure. The existing animal literature is controversial on the issue of pedicle vasospasm, with some authors reporting that the pedicle is alpha-agonist resistant 7 while other authors report that the pedicle is highly sensitive to alpha-agonists. 1 These changes in vessel sensitivity are presumed to occur secondary to the sympathectomy resulting from the dissection and division of the vascular pedicle.…”
Section: Discussionmentioning
confidence: 97%
“…5,6 The microvascular surgeon's fear of vasopressors likely stems from the belief that these drugs may provoke pedicle vasospasm, which can lead to thrombosis and flap failure. The existing animal literature is controversial on the issue of pedicle vasospasm, with some authors reporting that the pedicle is alpha-agonist resistant 7 while other authors report that the pedicle is highly sensitive to alpha-agonists. 1 These changes in vessel sensitivity are presumed to occur secondary to the sympathectomy resulting from the dissection and division of the vascular pedicle.…”
Section: Discussionmentioning
confidence: 97%
“…[29][30][31]33,73 Animal studies have demonstrated an attenuated response to norepinephrine and phenylephrine following surgical sympathectomy. 91 Following vasopressor administration, cutaneous microcirculation actually increased in an amount proportional to the change in mean arterial pressure in postsympathectomy tissue, whereas flow in normal tissue was reduced. When the effects of phenylephrine, dopamine, and dobutamine were compared in a swine musculocutaneous flap model, phenylephrine reduced cardiac output and flap flow.…”
Section: Vasopressorsmentioning
confidence: 98%
“…A similar effect has been observed when innervated and denervated pedicle flaps were raised in a rat model. 14 In these studies, the denervated flaps had an increase in blood flow after norepinephrine or phenylephrine (␣ 1 agonist) administration, with a simultaneous reduction in flow in the innervated flap. The effect was blocked by prazosin, a selective blocker of ␣ 1 receptors on vascular smooth muscle, suggesting the effect was due to a decreased sensitivity to ␣ 1 agonists.…”
Section: Mean (Sd) Hr (Beats/min) Systolic (Mmhg) Map (Mmhg) Co (Litementioning
confidence: 98%